2016
DOI: 10.1111/jpn.12521
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary Chlorella vulgaris supplementation on micro‐organism community, enzyme activities and fatty acid profile in the rumen liquid of goats

Abstract: Microalgae might be considered as an alternative source of fat and/or protein for ruminant's diets. However, changes in populations of ruminal micro-organisms associated with biohydrogenation process, methane and ammonia production in response to microalgae dietary supplementation have not been well characterized. Thus, 16 cross-bred goats were divided into two groups. Each goat of both groups was fed individually with alfalfa hay and concentrates separately. The concentrates of the control group had no microa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 58 publications
1
35
0
Order By: Relevance
“…Tsiplakou et al . (2016) observed an increased methanobacteria and protozoa population in the rumen liquid of goats fed a forage-based diet supplemented with C. vulgaris . Anele et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tsiplakou et al . (2016) observed an increased methanobacteria and protozoa population in the rumen liquid of goats fed a forage-based diet supplemented with C. vulgaris . Anele et al .…”
Section: Discussionmentioning
confidence: 99%
“…Besides this, and due to its high eicosapentaenoic and docosahexaenoic (DHA) contents, C. vulgaris has been considered as a possible additive for reduction of CH 4 emissions (Tsiplakou et al . 2016). This may be related to its content of unsaturated fatty acids, resulting in reduced CH 4 production (Martin et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2017a) observed an increase in methane production and Tsiplakou et al. () observed an increase in methane‐producing bacteria and protozoa with the supplementation of protein‐rich Chlorella vulgaris , indicating that not all microalgae are likely to have methane reducing properties. Data on methane production in this study showed a similar trend.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported a reduction of ruminal methanogenesis in vitro (Boeckaert et al, 2006;Fievez et al, 2007;Ungerfeld, Rust, Burnett, Yokoyama, & Wang, 2005) or in vivo (Elghandour et al, 2017) when microalgae rich in polyunsaturated fatty acids (docosahexaenoic acid, hexadecatrienoic acid) were supplemented. Nevertheless, Kholif et al (2017a) observed an increase in methane production and Tsiplakou et al (2016) observed an increase in methane-producing bacteria and protozoa with the supplementation of protein-rich Chlorella vulgaris, indicating that not all microalgae are likely to have methane reducing properties. Data on methane production in this study showed a similar trend.…”
Section: Production Of Volatile Fatty Acids and Methanementioning
confidence: 98%